Multifunctional nickel-phosphorus doped graphite-like carbon nitride nanosheets, preparation method thereof and ABS material
Through the preparation of phosphorus-nickel-doped graphite carbon nitride nanosheets, the problems of poor smoke suppression and low thermal stability during combustion of flame retardant ABS materials are solved, and the mechanical properties and resistance of ABS are improved under low addition amounts are achieved. Fueling performance, with wide industrial application prospects.
Patent Information
- Application Number
- CN202211000459.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-19
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-08-19
AI Technical Summary
The existing flame retardant ABS materials have poor smoke resistance and low thermal stability during combustion. Common flame retardants will sacrifice mechanical properties when improving flame retardancy, making it difficult to meet mechanical properties, thermal stability, flame retardancy and Smoke-resisting demand.
Using multifunctional phosphorus-nickel-doped graphite carbon nitride nanosheets (Ni-P-C3N4), the ABS material can be prepared with low addition amounts by urea calcining, stirring of sulfuric acid solution, sonication and modification of phosphorus and nickel elements. nanocomposites with thermal stability, mechanical properties and smoke suppression.
In composite materials, the introduction of Ni-P-C3N4 nanosheets has improved the heat resistance, carbonization ability and mechanical strength of ABS, reduced the heat release rate and smoke release rate, significantly improved the flame retardant performance and smoke suppression, and has Wide industrial application prospects.
Smart Images

Figure CN116178795B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardant materials and relates to a multifunctional nickel-phosphorus doped graphite-like carbon nitride nanosheet, a preparation method thereof and an ABS material. Background Art
[0002] Acrylonitrile-butadiene-styrene (ABS) copolymer is widely used in electronics, automobiles, aviation and other fields due to its light weight, good thermal stability, high mechanical properties and excellent chemical stability. However, ABS is flammable and releases a lot of heat and smoke during combustion. People have done a lot of work on the flame retardant development of ABS.
[0003] The introduction of flame retardants is an effective and simple method for preparing flame-retardant polymers. Halogenated compounds have high flame retardant efficiency and are widely used in the preparation of flame-retardant polymer materials. In recent years, some halogenated flame retardants have been banned due to their potential harm to the environment and humans, resulting in a variety of halogen-free alternatives, such as phosphorus (P), nitrogen (N) and metal compounds. However, these common flame retardants usually give polymers flame retardancy at the expense of mechanical properties. In order to avoid this defect, many nanomaterials with flame retardant and reinforcing effects (such as graphene, clay, boron nitride and carbon nanotubes, etc.) have been developed in recent years. However, most reported flame-retardant ABS composites have poor smoke suppression and low thermal stability. Therefore, it is particularly urgent to develop multifunctional nano-additives to improve the mechanical properties, thermal stability, flame retardancy and smoke suppression of ABS.
[0004] Graphitic carbon nitride (gC 3 N 4 ) as two-dimensional (2D) nanosheets, due to their high thermal stability, excellent chemical stability and excellent barrier effect, they show great potential in enhancing the flame retardancy of polymer materials. Similar to other nanomaterials, gC 3 N 4 It is necessary to dope flame retardants to improve their flame retardant efficiency and interfacial interaction with the polymer matrix. 3 N 4 / Polyaniline(gC 3 N 4 Preparation of poly(PANI@PA) hybrid materials and their application in intumescent flame-retardant epoxy coatings, a phytate zinc grafted gC 3 N 4 (gC 3 N 4 / PAZn) flame retardants, etc., although some encouraging progress has been made, gC 3 N 4 The flame retardant efficiency needs to be further improved, and based on gC3 N 4 The performance of flame retardant ABS cannot meet the demand well. Summary of the invention
[0005] The purpose of the present invention is to provide a multifunctional nickel-phosphorus doped graphite carbon nitride (Ni-PC) in view of the shortcomings of the prior art. 3 N 4 ) nanosheets, a preparation method thereof and ABS materials, wherein the nanosheets can simultaneously improve the mechanical properties, thermal stability, flame retardancy and smoke suppression of ABS.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A method for preparing multifunctional phosphorus-nickel doped graphite-like carbon nitride nanosheets comprises the following steps:
[0008] 1) Put urea in a covered crucible and calcine it in a muffle furnace. After cooling to room temperature, grind it to obtain blocky gC 3 N 4 powder;
[0009] 2) Block gC 3 N 4 The powder was stirred in a 25% sulfuric acid solution for at least 48 hours to form a suspension, and the supernatant was discarded by centrifugation. Distilled water was added and centrifuged again to remove the supernatant. The addition of distilled water and centrifugation were repeated until the supernatant became neutral. Finally, the solid product was dried and ground to obtain gC 3 N 4 Nanosheets;
[0010] 3) Toluene and gC 3 N 4 The nanosheets were placed in a three-necked round-bottom flask and ultrasonically treated for at least 10 minutes. Phosphorus oxychloride and triethylamine were added and stirred at room temperature for at least 30 minutes. The mixture was heated to 60°C and stirred for 3 hours. The crude product was filtered and washed several times with ethanol and dried to obtain phosphorus-grafted C 3 N 4 PC 3 N 4 Nanosheets;
[0011] 4) PC 3 N 4 The nanosheets were dispersed in distilled water, and after ultrasonic treatment, nickel nitrate aqueous solution was added and stirred for at least 2 h. The Ni-PC was collected by filtration. 3 N 4 The nanosheets were washed with ethanol and then dried.
[0012] In the above technical solution, further, in step 1), the calcination is carried out by heating the temperature to 420°C to 450°C at a heating rate of 5°C / min, and keeping the temperature at this temperature for 2 to 8 hours, then heating the temperature to 510°C to 540°C, and keeping the temperature for 3 to 6 hours to complete the reaction.
[0013] Furthermore, the centrifugation in step 2) is performed at a speed of 8000 rpm for 3 minutes.
[0014] Further, in step 3), toluene, gC 3 N 4 The usage ratio of nanosheets, phosphorus oxychloride and triethylamine is 100ml:3g:0.5g:3g.
[0015] Furthermore, in step 4), PC 3 N 4 The dosage ratio of nickel nitrate is 100:3~15.
[0016] Furthermore, the drying is: drying at 60° C. for 24 hours.
[0017] An ABS nanocomposite material, wherein the raw material of the material contains the above-mentioned multifunctional phosphorus-nickel doped graphite-like carbon nitride nanosheets.
[0018] Furthermore, the Ni-PC 3 N 4 The proportion of the nanosheets is 0.1wt% to 15wt%.
[0019] The beneficial effects of the present invention are:
[0020] The multifunctional P / Ni modified gC provided by the present invention 3 N 4 Nanosheets, adding them into ABS materials can improve the thermal stability, mechanical properties, flame retardancy and smoke suppression of polymer materials at the same time. Ni-PC uniformly dispersed in the composite material 3 N 4 Combined with gC 3 N 4 The physical barrier effect of the nanosheets and the catalytic carbonization effect of phosphorus and nickel elements can effectively improve the heat resistance, carbonization ability and mechanical strength of ABS at a low addition amount. 3 N 4 The TTI of the ABS / Ni-P-CN2 composite increased by 12 s, the PHRR and PSPR decreased by 32.4% and 33.8%, respectively. 3 N 4The introduction of also increases the tensile strength of the material by 24.3% and the initial degradation temperature by 15° C. The present invention can produce a high-performance polymer composite material and has a wide range of industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0022] Figure 1 The block gC in the present invention 3 N 4 , gC 3 N 4 Nanosheets, PC 3 N 4 and Ni-PC 3 N 4 FT-IR (a) and XPS (b) spectra of Ni-PC 3 N 4 High-resolution C1s(c), N1s(d), O1s(e), P2p(f) and Ni2p(g) XPS spectra of Ni-PC 3 N 4 (h) TEM micrograph, and Ni-PC 3 N 4 (i) STEM-HAADF image and the corresponding elemental maps of C, N, O, P, and Ni in the selected area.
[0023] Figure 2 TEM images of ABS / CN2 (a, b) and ABS / Ni-P-CN2 (c, d) composite materials in the present invention.
[0024] Figure 3 It is the XRD spectrum of ABS and the ABS composite material in the present invention.
[0025] Figure 4 1. The stress-strain curve (a) and tensile performance parameter (b) of ABS and the ABS composite material of the present invention.
[0026] Figure 5 ABS and the ABS composite material of the present invention are in N 2 TGA (a) and DTG (b) curves under different conditions.
[0027] Figure 6 The thermal radiation power is 35kW / m 2 When ABS and the ABS composite material of the present invention are heated to 100 ℃ and 80 ℃, the heat release rate (a) and smoke generation rate (b) curves, as well as the reduction range of heat release (c) and smoke generation rate (d) are shown.
[0028] Figure 7 These are the digital photos and scanning electron microscope photos of carbon residues after cone calorimetry test: ABS (a), ABS / CN2 (b), ABS / P-CN2 (c) and ABS / Ni-P-CN2 (d).
[0029] Figure 8 It is the infrared spectrum of carbon residue of ABS and ABS / CN2, ABS / P-CN2 and ABS / Ni-P-CN2 in the present invention. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0031] Urea, phosphorus oxychloride and sulfuric acid used in the following examples were provided by Shanghai Chemical Reagent Co., Ltd. (Shanghai, China). Nickel nitrate hexahydrate (Ni(NO 3 ) 3 6H 2 O) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (Shanghai, China). ABS resin (model: DG-417) was provided by Tianjin Dagu Chemical Co., Ltd. (Tianjin, China). Unless otherwise stated, all reagents were commercially available and used as received.
[0032] Example 1
[0033] A Ni-PC 3 N 4 Synthesis of nanosheets, including:
[0034] Step 1: Block gC 3 N 4 Manufacturing
[0035] 10 g of urea was placed in a covered crucible and calcined in a muffle furnace. The temperature was raised to 430 °C at a heating rate of 5 °C / min and kept at 430 °C for 4 h, then raised to 520 °C and kept for another 4 h to complete the reaction. After cooling to room temperature, a light yellow gC 3 N 4 powder.
[0036] Step 2: gC 3 N 4 Exfoliation of nanosheets
[0037] 1.0g block gC 3 N 4The powder was stirred in a 25% sulfuric acid solution for 48 hours to form a bright yellow suspension. The suspension was centrifuged at 8000 rpm for 3 minutes and the supernatant was discarded. Then, a certain amount of distilled water was added and centrifuged again to remove the supernatant. The above steps were repeated until the supernatant became neutral. Finally, the solid product was dried in a vacuum oven at 60°C for 24 hours and ground to obtain gC 3 N 4 Nanosheets.
[0038] Step 3: Phosphorus grafting C 3 N 4 (PC 3 N 4 ) Preparation of nanosheets
[0039] 100 ml of toluene and 3 g of C 3 N 4 The nanosheets were placed in a 300 ml three-necked round-bottom flask and ultrasonicated for 10 minutes. Then, 0.5 g of phosphorus oxychloride and 3 g of triethylamine were added and stirred at room temperature for 30 minutes. The mixture was heated to 60 ° C and stirred for 3 hours. After that, the crude product was obtained by filtration and washed with ethanol several times. After drying at 60 ° C for 24 hours, PC 3 N 4 Nanosheets.
[0040] Step 4: Ni / P doped C 3 N 4 (Ni-PC 3 N 4 ) Preparation of nanosheets
[0041] 1g PC 3 N 4 and 30 mL of distilled water were placed in a 50 mL flask and ultrasonically treated for 15 minutes for 3 times. Then nickel nitrate aqueous solution was added and stirred for 2 hours. Ni-PC was collected by filtration. 3 N 4 The nanosheets were then washed with ethanol and dried at 60 °C for 24 h.
[0042] Comparative Example 1
[0043] The steps in this example only include the first and second steps in Example 1, and the obtained product is gC 3 N 4 Nanosheets.
[0044] Comparative Example 2
[0045] The steps in this example only include the first, second and third steps in Example 1, and the obtained PC 3 N 4 Nanosheets.
[0046] Figure 1 a shows the blocky gC 3 N 4 , gC 3 N 4 Nanosheets, PC 3 N 4 and Ni-PC 3 N 4 FT-IR spectrum of bulk gC 3 N 4 and gC 3 N 4 Nanosheets at 3200 and 810 cm -1 The characteristic absorption peak is shown at 2 In addition to the above absorption peaks, PC 3 N 4 and Ni-PC 3 N 4 All at 1190cm -1 The P=O peak is shown at gC 3 N 4 Phosphorus doping of nanosheets. Figure 1 b shows the blocky gC 3 N 4 , gC 3 N 4 Nanosheets, PC 3 N 4 and Ni-PC 3 N 4 XPS full scan spectrum of bulk gC 3 N 4 It is composed of carbon (43.51 wt%), nitrogen (52.07 wt%) and oxygen (4.42 wt%) elements. The presence of oxygen is due to surface oxidation in air. 3 N 4 In comparison, due to acidification, gC 3 N 4 The oxygen content of the nanosheets increased. It is worth noting that carbon, nitrogen, oxygen, phosphorus and nickel can be found in the Ni-PC 3 N 4 The XPS spectrum of Ni-PC 3 N 4 The high-resolution XPS spectra of C1s, N1s, O1s, P2p and Ni2p are shown in Figure 1 As shown in c-1g. Ni-PC 3 N 4The C1s spectrum of gC is divided into four peaks. The peaks at 284.72, 285.43, 288.40 and 289.35 eV are attributed to CC / CH, COC / C-OH, NC=N and N=C(N)-NH, respectively, proving that gC 3 N 4 The N1s spectrum has three peaks, belonging to the sp 2 Bonded N atoms (398.76 eV), sp in N-(C)3 structure 3 The bonded N atom (399.53 eV) and the N atom in the CNH group (400.51 eV). The O1s spectrum shows a COC / C-OH peak at 531.92 eV. In addition, the peak of PO appears at 132.83 eV, and the Ni 2p 3 / 2 and Ni 2p 1 / 2 The peaks of Ni-PC are concentrated at 856.44 and 872.11 eV. The element quantitative results of XPS spectrum detection are shown in Table 1. These results all indicate that Ni-PC 3 N 4 Successful preparation.
[0047] Table 1. Quantitative comparison of elements detected from XPS spectra (in wt%)
[0048]
[0049] Figure 1 h and 1i show Ni-PC 3 N 4 TEM and STEM-HAADF images, and the corresponding elemental maps of the selected areas. 3 N 4 The flake-like gC 3 N 4 , and P and Ni atoms are evenly dispersed on the surface of the layer.
[0050] The gC prepared in each of the above examples was added to the ABS preparation by melt blending using a Thermo Hakker rheometer (temperature: 200°C, time: 12 minutes, rotor speed: 50 rpm). 3 N 4 、PC 3 N 4 and Ni-PC 3 N 4 Then, the nanocomposite was placed in a mold, preheated at 180°C for 6 minutes, and pressed at 12 MPa for 8 minutes to prepare a sample for subsequent testing. 3N 4 、PC 3 N 4 and Ni-PC 3 N 4 The nanocomposites are denoted as ABS / CN0.2, ABS / CN2, ABS / P-CN0.2, ABS / P-CN2, ABS / Ni-P-CN0.2 and ABS / Ni-P-CN2 respectively.
[0051] Figure 2 TEM images of ABS / CN2 and ABS / Ni-P-CN2 composites are shown. 3 N 4 Nanosheets tend to agglomerate in the ABS matrix, resulting in poor dispersion (see Figure 2 a and 2b). In contrast, Ni-PC 3 N 4 Evenly distributed in ABS, no large agglomerates were observed (see Figure 2 c), this is because Ni / P doping changes C 3 N 4 The surface functional groups and molecular polarity are more conducive to Ni-PC 3 N 4 Dispersion in ABS matrix. Figure 2 As shown in d, most Ni-PC 3 N 4 The nanosheets were peeled off as gray or black lines in the matrix. Apparently, phosphoric acid modification enhanced the Ni-PC 3 N 4 The interfacial interaction between the nanosheets and ABS significantly improved the Ni-PC 3 N 4 XRD was used to further study the dispersibility of functionalized gC 3 N 4 Dispersion in ABS matrix (such as Figure 3 ), no gC was found in the XRD patterns of ABS / CN2, ABS / P-CN2 and ABS / Ni-P-CN2 nanocomposites. 3 N 4 The characteristic diffraction peaks of nanosheets. This may be due to the fact that gC 3 N 4 The peak of Ni-PC is very weak and overlaps with the peak of ABS. 3 N 4 The nanosheets are evenly distributed in the ABS matrix.
[0052] The mechanical properties of polymer composites, especially mechanical strength, often determine their industrial applications. 3 N 4 、PC 3 N 4 and Ni-PC 3 N 4 The effect on the mechanical properties of ABS, the results are as follows Figure 4 As shown. Figure 4 As shown in a and 4b, the tensile strength (σ) and elongation at break or ductility (ε) of pure ABS are 58.5 MPa and 26.5%, respectively. 3 N 4 When the mass fraction of PC is 2wt%, the σ of ABS / CN2 increases by 10.2% and ε decreases by 41.9% relative to ABS. 3 N 4 The σ of ABS / P-CN2 can be increased by 20.0% and ε can be reduced by 54.0%. 3 N 4 ABS / Ni-P-CN2 exhibits the highest σ (72.7MPa), showing excellent mechanical strength. Obviously, Ni / P co-doping improves the 3 N 4 The interfacial interaction between the nanosheets and ABS leads to the Ni-PC 3 N 4 It can be well dispersed in the matrix and used as a reinforcing filler for ABS. 3 N 4 The outstanding reinforcing effect makes it superior to many traditional flame retardants, such as halogen-based and phosphorus-based compounds.
[0053] The thermal stability of ABS and its nanocomposites was studied by TGA technology. The curves and data are shown in Figure 5 and Table 2.
[0054] Table 2 N 2 Thermal stability data of ABS and its composites under atmosphere
[0055]
[0056]
[0057] a T i and b T max The temperatures are the temperatures at which 5 wt% loss and maximum weight loss occur, respectively.
[0058] All ABS composite materials are in N 2 The initial degradation temperature (T i ) and the maximum mass loss temperature (T max ) are 378℃ and 417℃ respectively. Functionalized gC 3 N 4 The introduction of ABS composites leads to the i and T max For example, T of ABS / P-CN2 i and T max The T of ABS / Ni-P-CN2 increased by 10℃. i and T max Increased by 15°C. T i and T max The increase is mainly due to gC 3 N 4 Physical barrier effect of nanosheets on thermal decomposition of ABS. It is worth noting that the T i and T max Both are higher than ABS / CN and ABS / P-CN, because Ni-PC 3 N 4 The dispersion in ABS matrix is better. In addition, the carbon residue of ABS at 600℃ is only 1.47wt%. 3 N 4 With the addition of Ni-PC, the carbon residue of ABS / Ni-P-CN2 increased to 5.18wt% at 600℃, which is 2.5 times that of ABS. 3 N 4 The promoting effect on ABS carbonization is better than gC 3 N 4 and PC 3 N 4 ABS / Ni-P-CN composite material has a higher carbon residue rate. It can be seen that the addition of Ni-PC 3 N 4 It can improve the thermal stability and carbon-forming ability of ABS at the same time.
[0059] Cone calorimeter for 35kW / m 2 The fire safety of ABS and its composite materials was evaluated under thermal radiation power. The results are as follows Figure 6 And as shown in Table 3.
[0060] Table 3 Cone calorimetry test results of ABS and its composites
[0061]
[0062] a TTI: ignition time, PHRR: peak heat release rate, THR: total heat release, AMLR: average mass loss rate, PSPR: peak smoke release rate, TSP: total smoke release
[0063] The TTI of pure ABS is 37s, indicating that it burns easily in fire. 3 N 4 The addition of gC and its derivatives increased the TTI of ABS composites. It can be seen that the TTI values of ABS / Ni-P-CN0.2 and ABS / Ni-P-CN2 increased to 47 and 49 seconds, respectively. The increase in TTI is mainly due to the 3 N 4 Physical barrier effect of nanosheets. Figure 6 As shown in a and Table 3, the PHRR of pure ABS is as high as 752kW / m 2 , while the PHRR of ABS / Ni-P-CN0.2 and ABS / Ni-P-CN2 decreased to 620 and 508 kW / m 2 , respectively, by 17.6% and 32.4% compared to ABS (see Figure 6 c). Similarly, the THR values of ABS / Ni-P-CN0.2 and ABS / Ni-P-CN2 are 7.6% and 9.5% lower than that of ABS, respectively. Figure 6 As shown in c, at the same addition amount, Ni-PC 3 N 4 The inhibitory effect on ABS heat release is better than gC 3 N 4 and PC 3 N 4 These results suggest that gC 3 N 4 , phosphorus and nickel together inhibit the heat release of ABS matrix during combustion. AMLR is usually used to reflect the overall fire intensity, as shown in Table 3. Obviously, the introduction of functional gC 3 N 4 The AMLR of ABS composites was reduced. After adding 2.0wt% Ni-P-C3N4, the AMLR of ABS / Ni-P-CN2 was reduced by 25.3% compared with ABS. 3 N 4 Significantly improves the flame retardant properties of ABS.
[0064] Thick smoke is one of the key factors leading to death in fire, so the present invention also studies gC in detail. 3 N 4 The effects of its derivatives on the smoke generation of ABS matrix are shown in the following table. Figure 6b and 6d and Table 3. The PSPR and TSP of pure ABS are as high as 0.296 m 2 / s and 44.2m 2 (See Table 3). Functionalized gC 3 N 4 The introduction of P / Ni co-doping significantly reduced the smoke emission of ABS. For example, compared with ABS, the PSPR and TSP of ABS / Ni-P-CN2 were reduced by 33.8% and 35.1%, respectively. 3 N 4 Shows better than gC 3 N 4 and PC 3 N 4 Better smoke suppression (see Figure 6 d) Therefore, Ni-PC 3 N 4 It also acts as a smoke suppressant during the combustion process.
[0065] It can be seen that Ni-PC 3 N 4 At the same time, the flame resistance, flame retardancy and smoke suppression of ABS are improved.
[0066] The present invention also studies the morphology and composition of the carbon residue obtained from the cone calorimetry test to reveal the functionalized gC 3 N 4 Effect of carbon residue formation on ABS matrix. Figure 7 Digital photos and SEM images of the carbon residues of ABS, ABS / CN2, ABS / P-CN2, and ABS / Ni-P-CN2 are shown, and the EDX data are listed in Table 4. After the cone calorimetry test, the original ABS was almost burned out, leaving a small amount of brittle and broken carbon residue (see Figure 7 a). At the same time, there are many micro cracks and holes on the surface of ABS carbon residue, such as Figure 7 As shown in the SEM image in a. 3 N 4 With the introduction of its derivatives, the density and continuity of ABS carbon are improved (see Figure 7 b-7d). In particular, the residual carbon of ABS / Ni-P-CN2 presents a dense continuous structure on the surface, which is conducive to suppressing heat release and smoke generation. Therefore, the significant improvement of flame retardancy and smoke suppression of ABS / Ni-P-CN2 is mainly due to the formation of this dense continuous carbon.
[0067] Table 4 EDX data of carbon residues of ABS and its composites
[0068]
[0069]
[0070] Table 4 lists the EDX data of carbon residues of ABS and its composites. The carbon and oxygen contents of pure ABS carbon residue are 68.86% and 31.14%, respectively. 3 N 4 With the addition of gC, the C content increased to 71.64wt% and the N content reached 2.17wt%. 3 N 4 It mainly acts in the condensed phase to delay the decomposition of the ABS matrix. 3 N 4 Replace gC 3 N 4 After that, the carbon content of the char further increased, indicating the catalytic carbonization effect of P. The carbon content of the ABS / Ni-P-CN2 residue was the highest, reaching 77.19wt%. At the same time, there were 2.93wt% P and 1.43wt% Ni in the char of ABS / Ni-P-CN2, which further confirmed that most of the P and Ni were retained in the condensed phase, promoting the carbonization of the ABS matrix. Figure 8 The FT-IR spectra of carbon residues of ABS, ABS / CN2, ABS / P-CN2 and ABS / Ni-P-CN2 are given. The carbon residue of ABS has the following wavelengths at 3440, 1600, 1260 and 970 cm -1 The characteristic absorption peaks are shown at 2200-2400 cm-1 and 1410 cm-2, respectively, belonging to OH / NH, C=C, COC and CC groups. For the carbon residues of ABS / CN2, ABS / P-CN2 and ABS / Ni-P-CN2, additional peaks (-C≡N and -C=N) appear at 2200-2400 cm-1 and 1410 cm-1. -1 , further indicating that gC 3 N 4 Remain in the coacervate phase to retard the decomposition of the matrix.
[0071] In summary, it can be seen that the present invention prepares an ABS composite material with excellent flame retardancy and smoke suppression. 3 N 4 Phosphorus and nitrogen co-doping can effectively improve its dispersibility in ABS and 3 N 4 The physical barrier effect of the nanosheets and the catalytic carbonization effect of phosphorus and nickel elements effectively improve the heat resistance, carbonization ability and mechanical strength of the final ABS composite material, which is conducive to its industrial application and promotion.
Claims
1. A method for preparing multifunctional phosphorus-nickel doped graphite-like carbon nitride nanosheets, characterized in that: The steps include: 1) placing urea in a covered crucible and calcining it in a muffle furnace, cooling it to room temperature, and then grinding it to obtain blocky g-C3N4 powder; 2) Stirring the blocky g-C3N4 powder in a 25% sulfuric acid solution for at least 48 hours to form a suspension, centrifuging and discarding the supernatant, adding distilled water and centrifuging again to remove the supernatant, repeating the addition of distilled water and centrifugation until the supernatant becomes neutral, and finally drying and grinding the solid product to obtain g-C3N4 nanosheets; 3) putting toluene and g-C3N4 nanosheets into a three-necked round-bottom flask and ultrasonically treating for at least 10 minutes, adding phosphorus oxychloride and triethylamine, stirring at room temperature for at least 30 minutes, heating the mixture to 60°C, and stirring for 3 hours, filtering to obtain a crude product, washing with ethanol several times, and drying to obtain phosphorus-grafted C3N4, i.e., P-C3N4 nanosheets; 4) P-C3N4 nanosheets are dispersed in distilled water, and after ultrasonic treatment, a nickel nitrate aqueous solution is added, stirred for at least 2 hours, filtered and collected to obtain Ni-P-C3N4 nanosheets, which are then washed with ethanol and dried.
2. The method for preparing multifunctional nickel-phosphorus doped graphitic carbon nitride nanosheets according to claim 1, characterized in that: In step 1), the calcination is carried out by heating the temperature to 420°C-450°C at a heating rate of 5°C / min and keeping the temperature at this temperature for 2-8 hours, then heating the temperature to 510°C-540°C and keeping the temperature for 3-6 hours to complete the reaction.
3. The method for preparing multifunctional phosphorus-nickel doped graphitic carbon nitride nanosheets according to claim 1, characterized in that: The centrifugation in step 2) is performed at a speed of 8000 rpm for 3 minutes.
4. The method for preparing multifunctional nickel-phosphorus doped graphitic carbon nitride nanosheets according to claim 1, characterized in that: The usage ratio of toluene, g-C3N4 nanosheets, phosphorus oxychloride and triethylamine in step 3) is 100ml:3g:0.5g:3g.
5. The method for preparing multifunctional nickel-phosphorus doped graphitic carbon nitride nanosheets according to claim 1, characterized in that: In step 4), the dosage ratio of P-C3N4 and nickel nitrate is 100:3-15.
6. The method for preparing multifunctional phosphorus-nickel doped graphitic carbon nitride nanosheets according to claim 1, characterized in that: The drying step is: drying at 60° C. for 24 hours.
7. An ABS nanocomposite material, characterized in that: The raw material of the material contains nanosheets obtained by any preparation method as described in claims 1-6.
8. The ABS nanocomposite material according to claim 7, characterized in that: The proportion of Ni-P-C3N4 nanosheets in the material is 0.1wt% to 15wt%.